Perceived Communication Barriers Between Nurses and Caregivers: Example of Pediatric Clinics - canan; ADIGÜZEL, Leyla; Canan DEMİRBAĞ, Birsel (Göbeklitepe Medical Science Journal, 2024)
This study aimed to determine the communication barriers perceived by nurses working in pediatric clinics and caregivers whose children are receiving inpatient treatment in these clinics. In the descriptive study conducted in a university hospital, the sample of the study consisted of 59 nurses and 203 caregivers. The data of the study was collected by face-to-face interview technique using the "Participant Questionnaire". The average age of the nurses participating in the study was 35.23+7.37, 93.2% were women, 61% were married, 76.3% had at least a bachelor's degree, 16.9% were not satisfied with working as a nurse, and 62.7% had poor communication skills during the education process. It was found that they received training and 27.1% thought they had difficulty communicating with caregivers. The average age of caregivers is 35.25+7.16, 83.7% are women, 57.2% are housewives, and 19.7% have difficulty communicating with nurses. It was determined that 96.6% of the nurses were working hard, 93.2% were tired, and 93.2% had difficulty communicating with caregivers due to the crowded and noisy environment. It was determined that 90.1% of the caregivers said that the nurses did not treat them with a friendly attitude, and 86.7% of them had difficulty in communicating because they did not show enough interest. A statistically significant difference was found between the nurses' gender, educational level, marital status and difficulty communicating with caregivers (p<0.05). As a result, it is recommended to increase the number of nurses working in clinics, regulate their working hours, and organize planned and regular training in the institutions where nurses work in order to improve their therapeutic communication skills.